2000
DOI: 10.1023/a:1007587523543
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: As the anionic PAMAM dendrimers displayed serosal transfer rates that were faster than observed for other synthetic and natural macromolecules (including tomato lectin) studied in the everted sac system, these interesting nanoscale structures may have potential for further development as oral drug delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(85 citation statements)
references
References 14 publications
3
82
0
Order By: Relevance
“…Full generation PAMAM dendrimers G4-G7, have previously been shown to have diameters of 4-8 nm [27], and similar to the results reported by Wiwattanapatapee et al [28], for G3.5 (4.0 nm) and G5.5 (6.7 nm) dendrimers, which are roughly in agreement with our results. In all cases, addition of cis-{Pt(NH 3 ) 2 } results in a decrease in the size of each dendrimer.…”
Section: Synthesis and Characterisation Of Drug-dendrimer Complexessupporting
confidence: 93%
“…Full generation PAMAM dendrimers G4-G7, have previously been shown to have diameters of 4-8 nm [27], and similar to the results reported by Wiwattanapatapee et al [28], for G3.5 (4.0 nm) and G5.5 (6.7 nm) dendrimers, which are roughly in agreement with our results. In all cases, addition of cis-{Pt(NH 3 ) 2 } results in a decrease in the size of each dendrimer.…”
Section: Synthesis and Characterisation Of Drug-dendrimer Complexessupporting
confidence: 93%
“…Conversely, anionic dendrimers showed greater serosal transfer rates than their tissue uptake in the same model. 28 This study confirmed the results from Caco-2 monolayer studies that PAMAM dendrimer's generation and surface charge influence their transepithelial transport.…”
Section: Translocation Of Pamam Dendrimers Across Isolated Intestinalsupporting
confidence: 88%
“…28 The results have shown that cationic PAMAM dendrimers exhibited greater tissue uptake than their serosal transfer rates across everted rat intestinal sacs at each time point. Conversely, anionic dendrimers showed greater serosal transfer rates than their tissue uptake in the same model.…”
Section: Translocation Of Pamam Dendrimers Across Isolated Intestinalmentioning
confidence: 87%
See 2 more Smart Citations